Pseudomonas syringae pv. tomato and the fall armyworm modulate the morpho-physiology and the metabolome of potato plants - Sandra Maluleke; Udoka Vitus Ogugua; Ntakadzeni Edwin Madala; Phumzile Sibisi; Mbalenhle Precious Mazibuko; Ebere Lovelyn Udeh; Robert Sicelo Nofemela; Khayalethu Ntushelo (PLoS ONE, 2025)
Potato seedlings were challenged with two parasites, namely, the fall armyworm and Pseudomonas syringae pv. tomato , in combination and individually. Growth (plant height, stem diameter, total number of tubers and total tuber weight) and physiological function (photosynthesis rate, stomatal conductance, transpiration efficiency, the ratio of intercellular CO 2 concentration to ambient CO 2 concentration (Ci/Ca) and water use efficiency) were measured to assess the effects of the parasites on the plants. A correlation analysis of the measured growth and physiology parameters was done to understand the co-ordination of the parasite-attacked plant processes. Finally, plant metabolomic profiles were determined to assess the effects of the parasites on the metabolomes of the treated plants. Individually and in combination, the parasites had varied effects on the growth and physiology of the plants. The correlation analysis also revealed key associations between the growth and physiology aspects, and the parasites caused metabolomic reprogramming in the treated plants. Some of the results were expected but there were also unexpected outcomes. Surprisingly, the pest drastically reduced plant height when administered alone, but its ability to reduce height lessened when it was co-administered with the bacterium. The lessened ability of the pest to reduce plant height in the presence of the bacterium hints at parasite-to-parasite antagonism. This same pattern extended to stem diameter and total tuber weight. The pest individually reduced stem diameter and total tuber weight, but not when co-administered. This also hints at parasite-to-parasite antagonism. However, this matter warrants further investigation. In conclusion, the pest and the pathogenic bacterium induce morpho-physiological and metabolomic changes in potato seedlings, their effects on the measured parameters vary, and there is a possible parasite-to-parasite antagonism.